Pengaruh Metode Simulasi Terhadap Tingkat Pengetahuan dan Keterampilan Bantuan Hidup Dasar (BHD) Anggota Palang Merah Remaja (PMR) - Hery Prayitno; Bintang Arya Nugraha (Jurnal Kesehatan, 2025)
The current problem in the field is the increasing number of cases of cardiac arrest and respiratory arrest in unexpected locations. However, only a small portion of the community, including teenagers, has the ability to provide basic life support. Through the learning simulation method, students can gain an overview of real situations in the form of cases and processes. This study aims to determine the effect of the simulation method on the level of knowledge and skills of BHD members of the Red Cross Youth (PMR) at SMAN 16 Bandung City. The research method is a quasi-experimental pretest-posttest without a control group. The number of samples is 19 members of the Red Cross Youth (PMR) at SMAN 16 Bandung City using a purposive sampling technique. Data collection uses a knowledge questionnaire and a skills observation sheet. The results of the study showed a significant increase in knowledge and skills in PMR members after the simulation method with the Paired T-test showing a p value = 0.000 (<0.05). There is an influence of the simulation method on the level of BHD skills of PMR members through the Wilcoxon Test showing a p value = 0.000 (<0.05). Conclusion: The simulation method is effective for use as an educational medium that uses artificial situations to improve the knowledge and skills of PMR members about BHD